2022
DOI: 10.1098/rsos.221083
|View full text |Cite
|
Sign up to set email alerts
|

Waking inactivity as a welfare indicator in laboratory mice: investigating postures, facial expressions and depression-like states

Abstract: Animal welfare assessment relies on valid and practical indicators of affect. In mice, the most widely used research vertebrates, lying still with eyes open, inactive-but-awake (IBA) in the home cage, has potential to be one such indicator. IBA is elevated in barren, conventional housing compared with well-resourced, enriched housing, and predicts immobility in Forced Swim Tests, a common measure of ‘helplessness’ in depression research. In Experiment 1, using females from three strains (C57BL/6, Balb/c and DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Psychomotor alterations in rodents can be evaluated in a stress-free way by using home cage monitoring systems (Fureix et al, 2022 ) (refer to the Home Cage Monitoring section). Importantly, it was observed that the inactive but awake state in the home cage predicted immobility in the FST (Maclellan et al, 2022 ).…”
Section: Depression-related Constructsmentioning
confidence: 99%
“…Psychomotor alterations in rodents can be evaluated in a stress-free way by using home cage monitoring systems (Fureix et al, 2022 ) (refer to the Home Cage Monitoring section). Importantly, it was observed that the inactive but awake state in the home cage predicted immobility in the FST (Maclellan et al, 2022 ).…”
Section: Depression-related Constructsmentioning
confidence: 99%